Quality of life in neuropathic pain: a literature review (Research, Society and Development, 2021)
Introduction: Neuropathic pain may develop after injury to the central nervous system, peripheral or both, when deleterious changes occur along the nociceptive modulatory pathways of the central nervous system. Proper management requires an interdisciplinary approach, as it can impact quality of life. Objectives: This review of the literature aims to assess the impact of pharmacological and non-pharmacological factors in the quality of life of patients with chronic neuropathic pain. Methodology: A systematized virtual search was carried out in PubMed®, collected articles between January 2010 and May 2020 using the terms “neuropathic pain”, “treatment”, “human” and “systematic review” using the filters of “systematic reviews ”E“ published in the last 10 years ”. All articles were formed by two independent reviewers and tabulated in a spreadsheet using Microsoft Excel® software. Results: Non-pharmacological interventions were addressed by most articles. Some articles addressed pharmacological interventions, with painful diabetic peripheral neuropathy being the main etiology. The most used quality of life measurement tools were: Medical Outcomes Study 36 (SF-36); EuroQol-5 Dimension (EQ-5D) and Beck Depression Inventory Score (BDI). Conclusion: The scarcity of high-quality studies that measure quality of life through validated tools is an obstacle to credible analysis of the impact of interventions on the life of chronic pain patients, however, in a preliminary way, cognitive behavioral therapy and the use of Spray THC/CBD oromucous has the potential to have a beneficial impact on quality of life.